An Evidence-Based Learning Perspective on the Relationship Between Profitability, EVA, and MVA with Stock Returns in Indonesia’s Mining Sector - Yulia, Amanda; Azis, Mohammad Taufik; Djajuli, Mohamad (CV. Tripe Konsultan, 2025)
This study aimed to examine the effect of Profitability, Economic Value Added (EVA), and Market Value Added (MVA) on stock returns in the mining sector listed on the Indonesia Stock Exchange (IDX) for the period 2021–2024. The data used is secondary data from the financial reports of companies in the mining sector listed on the IDX. The research sample consists of 38 companies with a study period of 4 years, resulting in 152 firm-year observations. The sample was selected using purposive sampling, with data obtained through the official IDX website. Panel data regression analysis and hypothesis testing were conducted using EViews 12SV software.The results show that profitability has a significant positive effect on the stock returns of mining sector companies. EVA has a negative but insignificant effect on stock returns, while MVA has a significant positive effect on stock returns. Simultaneously, profitability, EVA, and MVA have a significant positive influence on stock returns in the mining sector. This empirical evidence not only contributes to the literature on value-based performance measures but also provides a strong foundation for evidence-based learning in higher education. By linking valuation metrics with real-world stock performance, the study supports the teaching of corporate finance, capital markets, and financial literacy in an Indonesian context.